The Effects of Different Investment Materials on Dimensional Accuracy and Surface Roughness of Thermosens Maxillary Complete Dentures - Hamad , Thekra I; Fatihallah , Abdalbasit A; Abdulsahib , Ali J (Journal of Baghdad College of Dentistry, 2015)
Background: Limited data are available on the dimensional stability and surface roughness of ThermoSens, which is a material used in denture processing. This study aimed to measure the vertical teeth changes and surface roughness of ThermoSens dentures prepared using three different investment materials. Materials and methods: For the dimensional changes test, 30 complete maxillary dentures were prepared using different investment methods: group I, dental stone; group II, silicone putty; and group III, a mixture of dental stone and plaster (ratio, 1:1; n = 10 for each group). Four screws were attached to the dentures: two were attached to the buccal surface of the canine and first molar, and the other two were attached in the flange areas of the canine and first molar in line with the previously mentioned screws. Measurements were made using a micrometer microscope in the wax stage before flasking and in the deflasking stage. The above investment techniques were also used to prepare samples for a surface roughness test (n = 10 per group). These samples were prepared according to the specifications of the American Dental Association. Data were examined using analysis of variance (ANOVA) and the least significant difference (LSD) test. Results: One-way ANOVA and LSD revealed that dimensional changes significantly differed among all groups, except that the vertical teeth changes on the left side did not differ between groups I and II for both the canine and molar regions. Surface roughness was significantly higher in group I than in group II, and in group III than in group II. Conclusion: The use of putty silicone for investing ThermoSens complete dentures reduced dimensional changes and resulted in dentures with a better fit. Surface roughness could be reduced by the addition of a putty silicone layer over the denture before the addition of the second investment layer during denture processing.